Impact of socioeconomic deprivation on mechanical thrombectomy outcomes after acute ischaemic stroke: findings from a London-based multicentre study - Robert Simister; Viva Levee; Matthew Fallon; Soma Banerjee; Fahad Sheikh; Liqun Zhang; Lucio D’Anna; Tsering Dolkar; Katherine Chulack; Feras Fayez; Nina Mansoor; Adelaida Gartner (Stroke and Vascular Neurology)
Background Mechanical thrombectomy (MT) improves outcomes in patients who had an acute ischaemic stroke due to large vessel occlusion (LVO). However, socioeconomic status (SES) can influence recovery and prognosis. This study investigated the effect of SES, assessed via the Index of Multiple Deprivation (IMD), on MT outcomes in a multicentre London cohort.Methods This retrospective study included patients with anterior circulation LVO treated with MT between 2021 and 2023 at three London hospitals. Patients were grouped into IMD1–5 (more deprived) and IMD6–10 (less deprived). Inverse probability weighting balanced baseline characteristics. Primary outcomes were 90-day functional independence (modified Rankin Scale (mRS) 0–2) and 90-day mRS shift. Secondary outcomes included recanalisation, early neurological changes, 90-day mortality, symptomatic intracerebral haemorrhage (sICH) and haemorrhagic transformation (HT). Subgroup analyses explored interactions between IMD and demographic or clinical factors. LASSO (Least Absolute Shrinkage and Selection Operator) regression identified predictors of functional independence, while receiver operating characteristic analysis evaluated IMD’s predictive value.Results Among 1219 patients with acute LVO ischemic stroke treated with MT, 533 (43.7%) were in IMD1–5 and 686 (56.3%) in IMD6–10. IMD1–5 patients had lower odds of functional independence at 90 days (RR 0.79, 95% CI 0.70 to 0.90) and worse mRS shift (OR 1.29, 95% CI 1.06 to 1.58). They also had higher risks of sICH (RR 2.07, 95% CI 1.54 to 2.67) and HT (Risk Ratio 1.47, 95% CI 1.21 to 1.80). Subgroup analysis highlighted IMD’s predictive importance in Asian or mixed ethnicity groups. A model incorporating IMD, age, sex, hypertension and National Institutes of Health Stroke Scale (area under the curve 0.656) demonstrated predictive accuracy for 90-day functional independence.Conclusions Lower SES correlates with worse outcomes and higher complications post-MT, even within a universal healthcare system. Addressing SES disparities could improve stroke care equity.